Zeta potential of crude oil in aqueous solution - Collini,H; Jackson,MD (Advances in Colloid and Interface Science, 2023)
Despite the broad range of interest and applications, controls on the surface charge of crude oil in aqueous solution remain poorly understood. The primary data source to understand the surface charge on crude oil comprises measurements of zeta potential on individual drops or emulsions obtained using the electrophoretic method (EPM). Here we (i) collate and review previous measurements of zeta potential on crude oil, (ii) compare and contrast the results, and (iii) report new measurements of zeta potential on crude oil wetting films and layers relevant to oil-saturated porous media, obtained using the streaming potential method (SPM).Results show that the zeta potential depends on electrolyte pH and the concentration of divalent ions Ca2+ and Mg2+. Lower pH and higher concentration of these divalent ions yields more positive zeta potential. The isoelectric point (IEP) in simple NaCl electrolytes lies in the pH range 3–5. The IEP in simple CaCl2 and MgCl2 electrolytes can be expressed as pCa or pMg, respectively, and lies in the range 0–1. Close to the IEP, the zeta potential varies linearly with pH, pCa or pMg, suggesting simple Nernstian behaviour of the crude oil surface. The sensitivity of the zeta potential to pH, pCa and pMg decreases with increasing total ionic strength. The impact of pH, pCa and pMg on zeta potential varies significantly across different crude oils and differs from non-polar hydrocarbons. The potential for other multivalent ions to modify crude oil zeta potential has not been tested. Data for crude oil wetting films and layers, obtained using the SPM and strongly oil-wet porous substrates in which the solid surfaces are coated with the crude oil of interest, are comparable to those obtained using emulsions and the EPM, suggesting that the controls on zeta potential on crude oil are the same irrespective of whether the oil forms droplets or wetting layers.The literature data reviewed here, along with new measured data, provide imp